The literature of Ireland : culture and criticism - Brown, Terence, 1944- (Cambridge ; New York : Cambridge University Press, 2010)
"One of Ireland's foremost literary and cultural historians, Terence Brown's command of the intellectual and cultural currents running through the Irish literary canon is second to none, and he has been enormously influential in shaping the field of Irish studies. These essays reflect the key themes of Brown's distinguished career, most crucially his critical engagement with the post-colonial model of Irish cultural and literary history currently dominant in Irish Studies. With essays on major figures such as Yeats, MacNeice, Joyce and Beckett, as well as contemporary authors including Seamus Heaney, Derek Mahon, Michael Longley, Paul Muldoon and Brian Friel, this volume is a major contribution to scholarship, directing scholars and students to new approaches to twentieth-century Irish cultural and literary history"--
Machine generated contents note: Introduction; 1. The Literary Revival: historical reflections; 2. Joyce's magic lantern; 3. Music: the cultural issue; 4. Modernism and revolution: re-reading Yeats's 'Easter 1916'; 5. Shakespeare and the Irish self; 6. Irish literature and the Great War; 7. Irish modernism and the 1930s; 8. Post-modernists: Samuel Beckett and Flann O'Brien; 9. Patrick Kavanagh: religious poet; 10. MacNeice's Ireland: MacNeice's Islands; 11. Louis MacNeice and the Second World War; 12. MacNeice and the Puritan tradition; 13. John Hewitt and memory: a reflection; 14. Michael Longley and the Irish poetic tradition; 15. Seamus Heaney: the witnessing eye and the speaking tongue; 16. Derek Mahon: the poet and painting; 17. Telling tales: Kennelly's Cromwell and Muldoon's 'The More a Man Has the More a Man Wants'; 18. Redeeming the time: the novels of John McGahern and John Banvillle; 19. 'Have we a context': transition, self and society in the drama of Brian Friel; 20. Hubert Butler and nationalism; 21. The Irish Dylan Thomas: versions and influences.
Includes bibliographical references and index.
Keywords: English literature -- Irish authors -- History and criticism; Literature and society -- Ireland; Ireland -- In literature